Digital expansions of physical learning spaces in practice-based subjects - blended learning in Art and Craft & Design in teacher education - Nortvig, Anne-Mette; Petersen, Anne Kristine; Helsinghof, Helle; Brænder, Birgit (Computers and education, 2020)
Experimentation with learning designs in practical subjects has been given little attention in extant research literature on online and blended learning in teacher education. To meet this scarcity, the present paper presents findings from two learning design experiments in the subjects of Art and Craft & Design in teacher education in Denmark. The purpose of the experiments is to investigate how subject-specific, physical learning spaces can be expanded digitally in blended learning courses in practical subjects in which students must train their craftsman-like skills. The learning design experiment carried out in the subject of Art integrates art museums as physical spaces through the use of virtual reality (VR), whereas the learning design experiment in Craft & Design integrates practical workshops as physical spaces through the use of synchronous online webinars. The findings presented below show that the learning design experiments help integrate authentic learning spaces into the two subjects through the use of digital technology, albeit in different ways. In Art, the learning design tested is experienced as digitally expanded learning spaces by teacher students because the real world outside of campus (in this case, art museums) is integrated into an educational setting through the use of VR. In Craft & Design, the online webinars are experienced as authentic, digitally expanded learning spaces because they provide an opportunity to think and speak in the practical modes of the subject. •Descriptions and analyses of learning designs for the subjects of Art and Craft and Design.•Experiments with Virtual Reality and workshop webinar designs.•Integration of authentic learning spaces through the use of digital technology.•Design-based research conducted in collaboration between researchers and educators.•Mixed methods data.